Facile “Needle-Scratching” method for fast catalyst patterns used for large-scale growth of densely aligned single-walled carbon-nanotube arrays - Li, Bing (2012)
Scratching the surface: a simple needle-scratching method (NSM) generates large-area catalyst patterns on solid substrates for the growth of densely aligned single-walled carbon-nanotube (SWCNT) arrays by chemical vapor deposition (CVD, see picture). A high density of well-aligned, ultralong SWCNTs is obtained on single-crystal quartz. This NSM could allow the fast, cheap, and large-area fabrication of CNT-based nanodevices.